New Product Development Strategy of a Risky Early-Researched Product, Case Study : NPD Strategy Decision of Stem Cell-Related Products in BFM - Chairindy Pratomo, Luna; S. Hariandja, Evo (The Indonesian Journal of Business Administration, 2016)
Abstract. Using the case study of product development of stem cell in Indonesia, This paper will explain how to design New Product Development Strategy Framework to support decision-making activity of a challenging new product development in pharmaceutical business, considering its prospect on the market, market needs, technical requirements, risks, and also build a estimation plan of the project timeline to complete the project, as a project proposal to the management. The research provides new product development attributes measurement tools design which can be applied by pharmaceutical company, which could help the company to decide which product is the best options and fulfill its top management’s expectations. The tools used are corporate strategy alignment scorecard, company’s requirement concept selection and testing, and concept assessment based on company’s technical preferences. Based on the research, the chosen stem-cell related product concept which fulfill requirements and criteria of BFM is Conditioned Medium. Keywords : New Product Development Method, Decision Making, Stem Cell Development